Non-aqueous electrolyte and lithium ion battery containing the same

CN122907738APending Publication Date: 2026-10-13HEFEI SMOOTHWAY ELECTRONIC MATERIALS CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611145477.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

研究表明,FEC能在硅基负极表面参与形成更致密、更稳定的SEI层(通常富含LiF),有效改善电池的首次库伦效率和常温循环寿命,然而,FEC添加剂本身存在热稳定性较差的缺点

Benefits of technology

[0005]基于上述问题,本发明的目的在于提供一种非水电解液及锂离子电池,该非水电解液中的化合物A可解决FEC在高温下的不稳定性问题,尤其适用于改善高镍/硅基体系电池的高温循环及存储性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907738A_ABST
    Figure CN122907738A_ABST
Patent Text Reader

Abstract

The application provides a non-aqueous electrolyte and a lithium ion battery. The non-aqueous electrolyte comprises a lithium salt, a non-aqueous organic solvent and an additive. The additive comprises a compound A with a structural formula as shown in formula I and fluoroethylene carbonate, a and b are integers from 0 to 4, and a+b>0. The addition of the compound A to the fluoroethylene carbonate can effectively solve the instability problem of the fluoroethylene carbonate at high temperature. The components of the inorganic solid electrolyte interface film formed by the compound A can also alleviate the negative effects caused by the repeated expansion-shrinkage of a silicon-based negative electrode in the cycle, and are especially suitable for improving the high-temperature cycle and storage performance of a high-nickel / silicon-based system battery. Formula I.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of energy storage device technology, particularly to secondary batteries, and even more particularly to a non-aqueous electrolyte and a lithium-ion battery containing the non-aqueous electrolyte. Background Technology

[0002] With the increasing demands on lithium-ion battery performance from applications such as electric vehicles, portable electronic devices, and energy storage power stations, the development of lithium-ion batteries with wide temperature range, high rate capability, and high energy density has become a current research hotspot. Against this backdrop, the matching of high-nickel ternary cathode materials (with a nickel content higher than 50 wt.% in the transition metal) with silicon-carbon composite anode materials is considered one of the key technological pathways to achieve a power battery energy density exceeding 300 Wh / kg, as it can significantly improve battery energy density. The combination of high-nickel ternary cathodes and silicon-based anodes results in a higher inter-electrode potential difference and specific capacity. The theoretical specific capacity of silicon-based anodes is as high as 4200 mAh / g, approximately ten times that of traditional graphite anodes, significantly improving the energy density of single-cell batteries without changing the amount of inactive components. However, silicon-based materials experience significant volume changes during electrochemical cycling (expansion rate can reach over 300%), leading to structural failure of the anode material, pulverization of active particles, and deterioration of electrical contact. More critically, it is difficult for silicon-based anode materials to form a stable solid electrolyte interphase (SEI) film on their surface during cycling. Repeated volume expansion and contraction cause the SEI film to rupture and regenerate repeatedly. This process not only continuously consumes electrolyte and active lithium source, but also leads to increased ionic impedance, hindering lithium ion diffusion and ultimately accelerating the decay of battery capacity.

[0003] To improve the performance of the SEI film on the surface of silicon-based anodes, fluoroethylene carbonate (FEC) is often added to the electrolyte as a film-forming additive. Studies have shown that FEC can participate in the formation of a denser and more stable SEI layer (usually rich in LiF) on the surface of silicon-based anodes, effectively improving the initial coulombic efficiency and cycle life at room temperature. However, FEC additives themselves have the disadvantage of poor thermal stability. Under high-temperature conditions, FEC easily decomposes to produce acidic substances such as HF. These substances corrode the SEI film and the positive electrode electrolyte interface (CEI film), damage the structure of high-nickel positive electrode materials, and exacerbate the oxidative decomposition of the electrolyte, thereby causing problems such as battery gas generation and swelling.

[0004] To address the instability of electrode-electrolyte (FEC) at high temperatures while retaining its excellent film-forming properties at room temperature, researchers have begun developing novel composite additive systems. These studies aim to introduce thermally stable auxiliary additives to create a synergistic effect with FEC, jointly constructing a more robust electrode-electrolyte interface. Therefore, developing novel additive systems with superior thermal stability and interface protection functions has become a key direction for improving the overall performance of high-nickel / silicon-based batteries, particularly high-temperature cycling, storage performance, and gas generation suppression. Summary of the Invention

[0005] Based on the above problems, the purpose of this invention is to provide a non-aqueous electrolyte and a lithium-ion battery. Compound A in the non-aqueous electrolyte can solve the instability problem of FEC at high temperatures, and is particularly suitable for improving the high-temperature cycling and storage performance of high-nickel / silicon-based batteries.

[0006] To achieve the above objectives, the present invention provides a non-aqueous electrolyte comprising a lithium salt, a non-aqueous organic solvent, and an additive, wherein the additive comprises compound A with the structural formula shown in Formula 1 and fluoroethylene carbonate, where a and b are integers from 0 to 4, and a + b > 0.

[0007] Formula 1 The additive of this invention includes fluoroethylene carbonate (FEC), which effectively improves the initial coulombic efficiency and room-temperature cycle life of the battery. Additionally, compound A, with the structural formula shown in Formula 1, is added. This compound has an azole ketone cyclic structure and a fluorosulfonamide structure. Due to the presence of easily broken SF bonds and S, N, and O elements, a thin and dense inorganic solid electrolyte interface film is first formed during battery formation, protecting the positive and negative electrode interfaces and mitigating the corrosion of the interface caused by high-temperature acid production from FEC. Furthermore, compared to chain alkyl groups, the cyclic structure of the azole ketone is less prone to gas generation. The charge delocalization on its O and N atoms not only makes compound A more compatible with the negative electrode but also improves its stability to a certain extent and reduces the consumption of active lithium. Therefore, adding compound A to fluoroethylene carbonate can effectively solve its instability problem at high temperatures. The inorganic solid electrolyte interface film component formed by compound A can also alleviate the negative impact of repeated expansion and contraction of silicon-based anodes during cycling, and is especially suitable for improving the high-temperature cycling and storage performance of high-nickel / silicon-based batteries.

[0008] As one technical solution of the present invention, a and b are integers from 0 to 3, and a+b is 2 or 3.

[0009] As a technical solution of the present invention, compound A is selected from at least one of compounds one to six.

[0010]

[0011] Compound 1, Compound 2, Compound 3

[0012] Compound 4, Compound 5, Compound 6 As a technical solution of the present invention, based on the mass of the lithium salt, the non-aqueous organic solvent and the additive as 100%, the mass percentage of compound A is 0.05~5.00%, and the mass percentage of fluoroethylene carbonate is 1.0~10.0%.

[0013] As one technical solution of the present invention, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalate-borate), lithium difluorophosphate, lithium bis(oxalate-borate), lithium difluorooxalate-borate, lithium lower aliphatic carboxylic acids, lithium difluorobis(oxalate-phosphate), lithium bis(fluorosulfonyl)imide, lithium chloroborane, and lithium tetraphenylborate.

[0014] As a technical solution of the present invention, the non-aqueous organic solvent is selected from at least one of carbonates, carboxylic esters, lactones and ether compounds.

[0015] As a technical solution of the present invention, the non-aqueous organic solvent is selected from at least one of γ-butyrolactone, γ-valerolactone, δ-valerolactone, methyl acetate, ethyl acetate, ethyl propionate, butyl acetate, propyl propionate, butyl propionate, ethylene carbonate, propylene carbonate, butyl carbonate, methyl pentyl carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, propylene carbonate, 1,3-dioxolane, 1,4-dioxane, crown ether, tetrahydrofuran, 2-methyltetrahydrofuran, 2-trifluoromethyltetrahydrofuran, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether.

[0016] A second aspect of the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the electrolyte is selected from the aforementioned non-aqueous electrolytes.

[0017] As a technical solution of the present invention, the positive electrode sheet includes a positive electrode material, which is selected from at least one of lithium nickel cobalt manganese oxide materials, lithium nickel cobalt aluminum oxide materials, and lithium cobalt oxide materials.

[0018] As a technical solution of the present invention, the negative electrode sheet comprises a negative electrode material, and the negative electrode material is selected from at least one of artificial graphite, natural graphite, lithium titanate, elemental silicon, silicon-carbon composite material and silicon-oxygen composite material. Detailed Description of the Embodiments

[0019] The lithium-ion battery of the present invention comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. Wherein, the positive electrode sheet comprises a positive electrode material, and the positive electrode material is selected from at least one of lithium nickel cobalt manganese oxide series materials, lithium nickel cobalt aluminum oxide series materials and lithium cobalt oxide series materials. Further, the lithium nickel cobalt manganese oxide series material may include lithium nickel cobalt manganese oxide, doped or coated lithium nickel cobalt manganese oxide, and the lithium nickel cobalt aluminum oxide material may include lithium nickel cobalt aluminum oxide, doped or coated lithium nickel cobalt aluminum oxide. The chemical formula of the nickel-cobalt-manganese oxide is LiNi x Co y Mn z M (1-x-y-z) O2, and the chemical formula of the nickel-cobalt-aluminum oxide is LiNi x Co y Al z N (1-x-y-z) O2, wherein M is at least one of Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V and Ti, N is at least one of Mn, Mg, Cu, Zn, Sn, B, Ga, Cr, Sr, V and Ti, 0<x<1, 0<y<1, 0<z<1, x+y+z≤1. Still further, the lithium nickel cobalt manganese oxide series material may be LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2. The lithium cobalt oxide series material may include lithium cobalt oxide, doped or coated lithium cobalt oxide.

[0020] The negative electrode material is selected from at least one of artificial graphite, natural graphite, lithium titanate, elemental silicon, silicon-carbon composite material and silicon-oxygen composite material. Further, the negative electrode material at least contains elemental silicon, a silicon-carbon composite material or a silicon-oxygen composite material.

[0021] The non-aqueous electrolyte includes a lithium salt, a non-aqueous organic solvent and an additive.

[0022] The lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalato)borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium bis(oxalato)borate (LiBOB), lithium difluorooxalato)borate (LiDFOB), lower aliphatic carboxylic acids, lithium difluorodi(oxalato)phosphate (LiDFBP), lithium bis(fluorosulfonyl)imide (LiFSI), lithium chloroborane, and lithium tetraphenylborate. As an example, the lithium salt is lithium hexafluorophosphate (LiPF6), but not limited thereto. Furthermore, the lithium salt is a mixture of lithium hexafluorophosphate (LiPF6) and lithium bis(oxalato)borate (LiBOB), but not limited thereto. The lithium salt accounts for 5 to 25% of the total mass of the non-aqueous organic solvent, lithium salt, and additives. Further, the lithium salt accounts for 8 to 20% of the total mass of the non-aqueous organic solvent, lithium salt, and additives. Even further, the lithium salt accounts for 10 to 15% of the total mass of the non-aqueous organic solvent, lithium salt, and additives. For example, the lithium salt accounts for 5%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 20%, and 25% of the total mass of the non-aqueous organic solvent, lithium salt, and additives, but is not limited to the listed values. Other unlisted values ​​within this range also apply.

[0023] The non-aqueous organic solvent is selected from at least one of carbonates, carboxylic esters, lactones, and ethers. Further, the non-aqueous organic solvent is selected from γ-butyrolactone (GBL), γ-valerolactone (GVL), δ-valerolactone (DVL), methyl acetate (MA), ethyl acetate (EA), ethyl propionate (EP), butyl acetate (BAC), propyl propionate (PP), butyl propionate (PRB), ethylene carbonate (EC), propylene carbonate (PCA), butyl carbonate (BC), methyl pentyl carbonate (MPC), vinylene carbonate (VEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC). At least one of the following: methyl propyl carbonate (MPC), propylene carbonate (PC), 1,3-dioxolane (DOL), 1,4-dioxane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), 2-trifluoromethyltetrahydrofuran (2-CF3-THF), dimethoxymethane (DMM), diethoxymethane (DEM), ethoxymethoxymethane (DCE), ethylene glycol di-n-propyl ether (EDP), ethylene glycol di-n-butyl ether (EDB), and diethylene glycol dimethyl ether (DEGME). The non-aqueous organic solvent constitutes 65-90% of the total mass of the lithium salt, the non-aqueous organic solvent, and the additive; further, the non-aqueous organic solvent constitutes 75-89% of the total mass of the lithium salt, the non-aqueous organic solvent, and the additive; and even further, the non-aqueous organic solvent constitutes 78-88% of the total mass of the lithium salt, the non-aqueous organic solvent, and the additive. As an example, the non-aqueous organic solvent accounts for 65%, 70%, 80%, 85%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, and 90% of the total mass of the lithium salt, non-aqueous organic solvent, and additives, but is not limited to the listed values; other unlisted values ​​within this range also apply.

[0024] The additives include compound A and fluoroethylene carbonate. Based on the mass of lithium salt, non-aqueous organic solvent, and additives (100%), compound A comprises 0.05% to 5.00% by mass, and fluoroethylene carbonate comprises 1.0% to 10.0% by mass. For example, the mass percentage of compound A may be, but is not limited to, 0.05%, 0.10%, 0.30%, 0.50%, 0.70%, 1.00%, 1.50%, 2.00%, 2.50%, 3.00%, 3.50%, 4.00%, 4.50%, and 5.00%. The mass percentage of fluoroethylene carbonate may be, but is not limited to, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, and 10.0%.

[0025] The structural formula of compound A is shown in Formula 1, where a and b are integers from 0 to 4, and a + b > 0. Alternatively, a and b can be integers from 0 to 3, and a + b is 2 or 3. Further, when a is 0, b can be 1, 2, 3, or 4. When a is 1, b can be 0, 1, 2, 3, or 4. When a is 2, b can be 0, 1, 2, 3, or 4. When a is 3, b can be 0, 1, 2, 3, or 4. When a is 4, b can be 0, 1, 2, 3, or 4. When b is 0, a can be 1, 2, 3, or 4. When b is 1, a can be 0, 1, 2, 3, or 4. When b is 2, a can be 0, 1, 2, 3, or 4. When b is 3, a can be 0, 1, 2, 3, or 4. When b is 4, a can be 0, 1, 2, 3, or 4.

[0026]

[0027] Formula 1 Furthermore, compound A is selected from at least one of compounds one through six.

[0028]

[0029] Compound 1, Compound 2, Compound 3

[0030] Compound 4, Compound 5, Compound 6 The preparation method of compound one is as follows: Under an inert atmosphere, 0.2 mol of 2-azolidinone-thioyl fluoride (CAS No.: 710286-63-8) and a certain amount of bismuth trifluoride (0.14 mol) are mixed in a flask, stirred at 40-50°C for 3 h, then heated to 90-110°C and stirred for 12 h. The product is then obtained by distillation and fractional distillation. The retention time (8.31 min) of the characteristic peak and the purity are determined by gas chromatography.

[0031] Compounds two through six can be obtained by a similar method to compound one, and the preparation method is a synthetic procedure and specific method that should be readily available to those skilled in the art from relevant scientific literature or professional textbooks. Those skilled in the art will recognize that, based on general knowledge of organic synthesis, the compound preparation process can be optimized by adjusting the reaction conditions and sequence of steps in the synthetic strategy. The preparation process can be monitored using any appropriate scientific method known in the art. For example, the products can be monitored by gas chromatography, infrared spectroscopy, ultraviolet-visible spectrophotometry, nuclear magnetic resonance spectroscopy, high-performance liquid chromatography, or mass spectrometry.

[0032] To further illustrate the purpose, technical solution, and beneficial effects of this invention, the following will provide a further description of the invention in conjunction with specific embodiments. It should be noted that, for other raw materials in the embodiments and comparative examples where specific conditions are not specified, they can be carried out under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used where the manufacturer is not specified are all commercially available conventional products.

[0033] Example 1 (1) Preparation of non-aqueous electrolyte In an argon-filled glove box (O2 < 1 ppm, H2O < 1 ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and propylene carbonate (PC) were mixed in a weight ratio of EC:EMC:PC = 2:16:1 to obtain 81 g of non-aqueous organic solvent. Then, 0.5 g of compound I and 6 g of FEC were added, dissolved, and stirred thoroughly. After that, 12.5 g of lithium hexafluorophosphate was added and mixed evenly to obtain a non-aqueous electrolyte.

[0034] (2) Preparation of the positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O2, binder PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 95:1:4 to prepare a lithium secondary battery positive electrode slurry of a certain viscosity. The mixed slurry is coated on both sides of aluminum foil, dried and rolled to obtain the positive electrode sheet.

[0035] (3) Preparation of negative electrode Artificial graphite, CVD vapor-deposited pure silicon, conductive agent Ketjen black, binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose (CMC) are thoroughly mixed in a deionized water solvent system at a mass ratio of 74:20:2:1:1. The mixture is then coated onto copper foil, dried, and cold-pressed to obtain the negative electrode sheet.

[0036] (4) Preparation of lithium secondary batteries The positive electrode, separator, and negative electrode are stacked in sequence and then wound to form a soft-pack battery cell. The cell is packaged in a polymer aluminum-plastic film and filled with the non-aqueous electrolyte prepared above. After formation, capacity testing and other processes, a lithium-ion battery with a capacity of 1000mAh is produced.

[0037] The composition and content of the electrolytes in Examples 1-12 and Comparative Examples 1-4 are shown in Table 1. The preparation processes of the non-aqueous electrolytes, positive electrode sheets, negative electrode sheets, and lithium-ion batteries in Examples 2-12 and Comparative Examples 1-4 are the same as those in Example 1.

[0038] Table 1. Composition of the electrolytes in Examples 1-12 and Comparative Examples 1-4

[0039] Compound 7 is N,N-dimethylaminosulfonyl fluoride, with the structural formula shown below.

[0040]

[0041] The lithium-ion batteries prepared in Examples 1-12 and Comparative Examples 1-4 were subjected to performance tests under the following conditions, and the results are shown in Table 2.

[0042] (1) High-temperature cycling performance test A lithium-ion battery was charged at a constant current of 1.0C to a voltage of 4.2V at a constant temperature of 25℃, then charged at a constant voltage of 4.2V to a current of 0.05C, and then discharged at a constant current of 1.0C to a voltage of 3.0V. The first discharge capacity of the battery was recorded as C0. The lithium-ion battery was placed in a constant temperature chamber at 45℃ and left to stand for 30 minutes to allow it to reach a constant temperature. Then, it was cycled 300 times at 1.0C / 1.0C at 45℃. Finally, it was discharged at a constant current and constant voltage of 1.0C / 1.0C to 3V at a constant temperature of 25℃, and the discharge capacity was recorded as C1. The capacity retention rate of the lithium-ion battery after 300 cycles at 45℃ was calculated using the following formula.

[0043] Capacity retention rate = C1 / C0 × 100% (2) High-temperature storage performance test At a constant temperature of 25℃, the lithium-ion battery underwent one 0.3C / 0.3C charge and discharge cycle (battery discharge capacity recorded as C0), with an upper limit voltage of 4.2V. Then, the battery was charged to 4.2V under constant current and constant voltage conditions at 0.5C, and the battery thickness was measured (thickness recorded as D0). The battery was placed in a 60℃ oven for 30 days, removed, and its thickness measured (thickness recorded as D1). The battery was then placed in a 25℃ environment and discharged at 0.3C, with the discharge capacity recorded as C1. The lithium-ion battery was then subjected to one 0.3C / 0.3C charge and discharge cycle (battery discharge capacity recorded as C2), with an upper limit voltage of 4.2V. The thickness expansion rate, capacity retention rate, and capacity recovery rate of the lithium-ion battery were calculated using the following formulas.

[0044] Thickness expansion rate = (D1 - D0) / D0 × 100% Capacity retention rate = C1 / C0 × 100% Capacity recovery rate = C2 / C0 × 100% Table 2 Performance test results of lithium-ion batteries in Examples 1-12 and Comparative Examples 1-4

[0045] As shown in Table 2, the lithium-ion battery with compound A added to the FEC exhibits excellent high-temperature cycling and storage performance. This is because compound A possesses both an azole ketone cyclic structure and a fluorosulfonamide structure, and the specific functions of its groups effectively address the instability of FEC at high temperatures. In contrast, compounds 7 in Comparative Examples 3-4 only possess a fluorosulfonamide structure and lack an azole ketone cyclic structure, resulting in poor stability and an inability to resolve the gas generation problem at high temperatures.

[0046] Comparing Examples 1-6, it can be seen that when compound A is compound one or compound three, the battery performance is better. This is because its charge delocalization produces a more stable molecular structure, which further reduces the consumption of active lithium and the generation of gas, thus better improving the high-temperature cycling and high-temperature storage performance.

[0047] Comparing Examples 6 and 7, it is evident that the lithium salt combination of LiPF6 and LiBOB exhibits superior performance, particularly in high-temperature performance compared to the single LiPF6 system. This is because LiBOB, with its excellent thermal stability and unique molecular structure, effectively removes harmful HF generated during the thermal decomposition of LiPF6 and under high-temperature FEC conditions, further preventing HF erosion of the electrode materials and further decomposition of the electrolyte. Simultaneously, LiBOB preferentially decomposes on the positive and negative electrode surfaces before the electrolyte solvent, participating in the construction of a dense, borate-rich solid electrolyte interphase (SEI) film. This SEI film possesses excellent mechanical strength and high-temperature stability. Combined with the low-impedance, high-ionic-conductivity interfacial film formed by compound A, the interfacial impedance of the LiBOB film is effectively reduced. The synergistic effect of these multiple mechanisms significantly improves the capacity retention and impedance stability of the battery cell during high-temperature cycling.

[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A non-aqueous electrolyte, characterized in that, The mixture includes lithium salts, non-aqueous organic solvents, and additives, wherein the additives include compound A with the structural formula shown in Formula 1 and fluoroethylene carbonate, where a and b are integers from 0 to 4, and a + b > 0. Formula 1.

2. The non-aqueous electrolyte according to claim 1, characterized in that, a and b are integers from 0 to 3, and a+b is 2 or 3.

3. The non-aqueous electrolyte according to claim 1, wherein compound A is selected from at least one of compounds one to six. Compound 1, Compound 2, Compound 3 Compound four, compound five, compound six.

4. The non-aqueous electrolyte according to claim 1, characterized in that, Based on the mass of the lithium salt, the non-aqueous organic solvent, and the additives being 100%, the mass percentage of compound A is 0.05~5.00%, and the mass percentage of fluoroethylene carbonate is 1.0~10.0%.

5. The non-aqueous electrolyte according to claim 1, characterized in that, The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalate-borate), lithium difluorophosphate, lithium bis(oxalate-borate), lithium difluorooxalate-borate, lithium lower aliphatic carboxylic acids, lithium difluorobis(oxalate-phosphate), lithium bis(fluorosulfonyl)imide, lithium chloroborane, and lithium tetraphenylborate.

6. The non-aqueous electrolyte according to claim 1, characterized in that, The non-aqueous organic solvent is selected from at least one of carbonates, carboxylic esters, lactones, and ether compounds.

7. The non-aqueous electrolyte according to claim 6, characterized in that, The non-aqueous organic solvent is selected from at least one of γ-butyrolactone, γ-valerolactone, δ-valerolactone, methyl acetate, ethyl acetate, ethyl propionate, butyl acetate, propyl propionate, butyl propionate, ethylene carbonate, propylene carbonate, butyl carbonate, methyl pentyl carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, propylene carbonate, 1,3-dioxolane, 1,4-dioxane, crown ether, tetrahydrofuran, 2-methyltetrahydrofuran, 2-trifluoromethyltetrahydrofuran, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether.

8. A lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The electrolyte is selected from the non-aqueous electrolyte described in any one of claims 1 to 7.

9. The lithium-ion battery according to claim 8, characterized in that, The positive electrode sheet contains a positive electrode material, which is selected from at least one of lithium nickel cobalt manganese oxide materials, lithium nickel cobalt aluminum oxide materials, and lithium cobalt oxide materials.

10. The lithium-ion battery according to claim 8, characterized in that, The negative electrode sheet contains a negative electrode material, which is selected from at least one of artificial graphite, natural graphite, lithium titanate, elemental silicon, silicon-carbon composite material, and silicon-oxygen composite material.